Electron emission modulation effects in micro-size structures - Hartnagel, H. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A promising application of field-emission phenomena is microwave high-frequency oscillation generation. In this presentation, new effects at the field emission, as a perspective mechanism of high-frequency oscillation generation, has been investigated and analyzed. The mechanisms are connected with the generation of oscillations in field emission structures (i) based on the silicon or GaAs tips with ultrathin diamond-like carbon (DLC) films, (ii) III-V semiconductors (GaAs, GaN) and (iii) SiGe materials.